Homoiōsis Theōi: Plato's Ultimate Educational Aim. - Itao, Alexis Deodato S. (Problems / Problemos, 2023)
Many academics and researchers who publish scholarly articles on Plato's philosophy of education claim that the ultimate educational goal for Plato is simply the acquisition of virtues. While such a claim may not be entirely incorrect, it is nevertheless substantially wanting; for although the acquisition of virtue is no doubt paramount, for Plato it primarily serves as a means to another end. In this paper, I aim to show that, for Plato, the final summit of all educational enterprise is not really to become virtuous but rather to attain the state of becoming like God, and that is, homoiōsis theōi.